Potentials of Bamboo and Its Ecological Benefits in a Sustainable Green Economy - Mugunthan, Perumal; Mohd Effendi, Wasli; Johari, Zainudin (Institut EkoSains Borneo, Universiti Putra Malaysia Bintulu Sarawak Campus, 2023)
Bamboo is also known as “green gold”, “poor man’s timber”, “wonder plant”, contributes substantially to ecological sustainability because of its uniqueness in providing environmental, economic, and social benefits to mankind (Scheba et al., 2017; Manandhar et al., 2019). It offers ecological benefits such as soil conservation and carbon sequestration. Due to its rapid growth rate and organic content, bamboo can be used as a potential tool for mitigating climate change, which also helps to reduce soil erosion and enhance soil quality. Bamboo is widely acknowledged as a green substitute for conventional building materials because of its wood-like attributes, environmentally friendly growing, and sustainable harvesting. Although bamboo is not regarded as wood, it is a fast-growing species of woody grass that can be utilised as an excellent raw material distribution, reducing the demand for wood and wood products as well as the high rate of forest degradation. Bamboo has been dubbed one of the fastest-growing plants on Earth with a short gestation time (3 to 5 years) before reaching maturity and harvest (Atanda, 2015). It may be harvested and replanted in seven years due to its rapid growth, unlike certain indigenous tree species’ 10 to 50 years (Mohamed, 2003; Basumatary et al., 2015). Hence, this makes it appropriate for afforestation purpose.